Intraspinal air after blunt thoracic trauma - Krasoudakis A; Marathianos S; Tsiminikakis N; Chavredakis E; Arhontakis G (Wolters Kluwer Medknow Publications, 2006)
Presence of intraspinal air (pneomorachis) is usually iatrogenic after epidural injections or spinal manipulations. It may also be associated with degenerative disc disease, epidural abscess and synovial cysts. Presented herein is a case of a child with pneomorachis following blunt thoracic trauma.